Communication Strategies of Mothers as Single Parents in Socializing Life Values to Children (A Study of Fatherless Families) - Wirda Delima; Lahmuddin Lahmuddin; Cut Metia (Bulletin of Counseling and Psychotherapy, 2025)
The increasing prevalence of fatherless families in urban Indonesian contexts presents significant challenges for the transmission of life values and social norms to children, particularly as mothers assume dual parental roles amid persistent social stigma. This qualitative research with a phenomenological approach aims to analyze the communication strategies implemented by single mothers in socializing life values to children within the context of fatherless families in Medan City, Indonesia. Data were collected through in-depth interviews with 15 female heads of households and participant observation, then analyzed using thematic analysis techniques. The research findings reveal five main communication strategies: first, androgynous communication strategies that contextually integrate feminine (empathetic and dialogic) and masculine (firm and directive) characteristics; second, the construction of compensatory communication networks by involving significant male figures from extended families and communities; third, synergistic integration of verbal and non-verbal communication through behavioral modeling and reflection; fourth, creative adaptation of local cultural values (dalihan na tolu and musyawarah) modified according to the fatherless family structure; and fifth, the development of resistance narratives against social stigma through the construction of positive family identity. This study concludes that the success of value socialization in fatherless families highly depends on the mother’s ability to develop resilient, contextual communication strategies integrated with the sociocultural environment. These findings highlight the importance of developing support models for fatherless families that are grounded in existing strengths and local sociocultural potentials.